(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
Modern residential buildings are increasingly equipped with specialized climate control systems. Such systems are constantly becoming more complicated and nowadays allow to control and, if necessary, maintain at a given level a whole series of parameters in structures - temperature and humidity of air, its degree of purity and ionization, temperature and quality of water, level of illumination and irradiation, as well as technical design parameters. Placement of such climate control systems for low-rise residential buildings is assumed in the building itself, but for high-rise buildings such systems are placed on the roof. In this case, the practical task of protecting climate control systems from the dangerous action of aggressive external factors arises. The paper proposes the development of a special protective lantern capable of performing such a function. Structurally, the lantern consists of a steel frame made of bent-welded square profiles and translucent filling. Four architectural and constructive versions of the protective lantern are considered - arched, pyramidal-elongated, pyramidal and spherical. To select the most rational constructive option, numerical modeling was performed based on the finite element method using the domestic software product SCAD. Its results made it possible to choose the necessary cross- sections of the frame elements in accordance with the construction current standards in Ukraine. Based on the comparison of mass indicators and the market value of protective lantern materials, it was finally determined that the spherical lantern has the lowest indicators and is the most rational. However, for real buildings that have rectilinear load-bearing structural elements, this option may not be effective and may require reworking of the load-bearing structures. Therefore, for practical implementation an arched design version of the protective lantern was chosen. This option is recommended for practical implementation in the reconstruction project of a multi-story commercial-office-hotel complex in the city of Pavlograd.